HB Sebagai Salah Satu Faktor Kelelahan pada Pasien Kanker Payudara yang Menjalani Kemoterapi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze factors related to fatigue. This research method is quantitative analytical with correlational descriptive preparation using a cross-sectional approach. The results showed that HB caused a low decline in condition, the leading risk factor for fatigue. Bivariate analysis showed there was no relationship between age and fatigue (p 0.902), there was a relationship between HB and fatigue (p 0.03), there was no relationship between BMI and fatigue (p 0.155), there was no relationship between length of treatment and fatigue (p 0.091), there is no relationship between the independent variables and the dependent variable. In conclusion, there is no relationship between the independent and dependent variables. Keywords: HB, Breast Cancer, Fatigue, Chemotherapy